Effect of Working Capital Management on the Financial Performance of Selected Small and Medium Enterprises in Mukono District: A Case Study of Small And Medium Sized Enterprises, Mukono - Patience Owomugisha (Uganda Christian University, 2023)
The study investigated the effect of working capital management on the financial performance of selected Small and Medium Enterprises in Mukono District. The main objective of the study was to examine the effect of working capital management on financial performance on small and medium enterprises in Mukono guided by four specific objectives which were; To assess the influence of accounts payable management on the financial performance of small and medium enterprises, To examine the influence of accounts receivables management of the financial performance of small and medium enterprises, To analyze the influence of cash management on financial performance of small and medium enterprises and to assess the role of inventory management on financial performance of small and medium enterprises. A population of 100 employees / owners of SMEs was targeted but only a sample of 80 respondents was used. The study used Simple random sampling technique were all members of the finite population were given equal chances to be included in the sample since the target respondents were either engaged or had an idea about financial performance of SMEs and these were in a better position to respond to the research questions appropriately. Data was collected from primary and secondary sources through use of Questionnaire, interview Guide and observation. The data collected was then analyzed using SPSS for means to determine the level of dependent and independent variables. The findings of the study revealed that there is a significant relationship existing between working capital management and financial performance of the selected SMEs however it turned out that working capital management has been associated with a number of challenges such as lack of proper management practices, employing none professional staffs, etc. The researcher recommended that Small and Medium enterprises should manage their debts, receivables, cash and inventory retention very well in order to improve their financial performance as discussed in-depth in the main context.
This is a dissertation.